Phenotypic and Proteomic characterization of Clinical Candida albicans isolates resistant to Fluconazole - Geukgeuzian, Giovanni (2021)
The opportunistic fungal pathogen Candida albicans is a major causative agent of death in immunocompromised individuals. The azole fluconazole is the first line of defense in hospital treatment. Azoles function by inhibiting Erg11 an enzyme involved in the synthesis of ergosterol, the main sterol found in fungi. Resistance to azoles is on the increase worldwide including in Lebanon. The purpose of the current study is to determine pathogenicity attributes of azole resistant isolates from Lebanese hospital patients. Six isolates-3 resistant and 3 sensitive-underwent a battery of phenotypic tests related to virulence. In addition, the cell wall proteome of all isolates was isolated and underwent profiling by MALDI TOF TOF mass spectrometry to detect different proteins in resistant versus sensitive isolates, and differential presence in response to fluconazole exposure. Our results showed that resistant isolates had increase ergosterol content, and a slight increase in chitin deposition leading to resistance, but were on average attenuated in virulence compared with sensitive isolates. In addition, proteomic profiling revealed the presence of efflux pumps such as Cdr1, and Cdr2 exclusively in resistant isolates, an additional mechanism of resistance, and virulent isolates expressed more virulence genes as opposed to virulence attenuates isolates that did not express any. In conclusion, our study suggests several mechanisms of antifungal drug resistance in C. albicans Lebanese hospital isolates.